Hard alloy films with enhanced resistance to cracking. (June 2021) - Musil, J.; Čiperová, Z.; Čerstvý, R.; Kos, Š.
Abstract: The article reports on the mechanical properties of alloy films prepared by magnetron sputtering. Cracking is a great drawback of alloy films because it strongly limits many of their practical applications. It is shown that hard alloy films resistant to cracking must be superelastic and exhibit a high ratio H/E* ≥ 0.1; here H is the hardness and E* is the effective Young's modulus of the film. As examples, mechanical properties of the Si-based hard alloy films with enhanced resistance to cracking are given. Furthermore, the effect of the addition of Si and N into single element Mg films on the film mechanical properties and its relation to the changes of the material homologous temperature is investigated. Highlights: Mg alloy films. Addition of Si and N into Mg increases the hardness of Mg–Si–N alloy films. Mechanical properties of Mg–Si–N alloy films strongly depend on homologous temperature Ts /Tm . Addition of Si and N into Mg converts brittle alloy into hard, superelastic alloy even at RT.